2009
DOI: 10.1021/ic9002093
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of a Dimolybdenum SO Bridge, Subsequent Reactions, and Characterization of the Thioperoxide Bridge

Abstract: The SO bridge of the complex, [Mo(2)(NTo)(2)(S(2)P(OEt)(2))(2)(mu-O(2)CMe)(mu-SBn)(mu-SO)], 1, displayed nucleophilicity at O, giving alkylation products [Mo(2)(NTo)(2)(S(2)P(OEt)(2))(2)(mu-O(2)CMe)(mu-SBn)(mu-SOR)](+), 4(+), which contained the thioperoxide bridge. These cations were then subject to nucleophilic attack by two pathways. Debenzylation of the bridge thiolate in 4(+) afforded neutral [Mo(2)(NTo)(2)(S(2)P(OEt)(2))(2)(mu-O(2)CMe)(mu-S)(mu-SOR)], 5; de-esterification of a dithiophosphate ligand in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Therefore, it can act as a bi-radical ligand and tends to form compounds in which sulfur monoxide is bridged between two metal centers. 23–26 Furthermore, previous research showed that the Be–S bonds are sufficiently strong, and therefore, structures formed from this bond are thermodynamically stable. 21 So, in light of theoretical research on compounds with Be–Be bonds, the end-on sulfur-bound sulfur monoxide complex of Be 2 ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can act as a bi-radical ligand and tends to form compounds in which sulfur monoxide is bridged between two metal centers. 23–26 Furthermore, previous research showed that the Be–S bonds are sufficiently strong, and therefore, structures formed from this bond are thermodynamically stable. 21 So, in light of theoretical research on compounds with Be–Be bonds, the end-on sulfur-bound sulfur monoxide complex of Be 2 ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We have also examined the reactivity of our novel cis ‐thiohyponitrite complex 40 . Remarkably, gentle thermolysis of 40 in C 6 H 6 results in extrusion of N 2 from the [SNNO] 2– ligand, and formation of [K(18‐crown‐6)][ t Bu LNi(η 2 ‐SO)] ( 47 ) (Scheme ), a rare example of a structurally characterized thioperoxide complex . Significantly, addition of excess CO to 47 results in O‐atom abstraction and re‐formation of the terminal sulfide 32 , along with CO 2 .…”
Section: Synthesis and Structure Of M=s Complexesmentioning
confidence: 99%